The Saints of Rattlesnake Mountain : Stories - Waters, Don, 1974- (Book collections on Project MUSE., 2017)
Master storyteller Don Waters returns to the desert in his third book set in the American Southwest. With the gothic sensibility of Flannery O'Connor and emotional delicacy of Raymond Carver, these nine contemporary stories deftly explore the lives of characters losing or clinging to a fleeting faith and struggling to find something meaningful to believe in beneath overpowering desert skies. Soldiers, seekers, priests, prisoners, and surfers pursue their fate amid bizarre, sometimes overwhelming circumstances. In "La Luz de Jesús," a gutless Los Angeles screenwriter, a believer in nothing but the god of Hollywood, must reorient after he encounters a group of penitents in New Mexico's Sangre de Cristo Mountains. The decorated soldier in "Española" faces more chaos back home than he did during his tour in Iraq. And "The Saints of Rattlesnake Mountain" pairs a "trustee" prison inmate and a wild mustang horse, both wards of the state of Nevada, as they fumble toward a spiritual truth. These stories capture the spirit of a region and its people. Once again Waters assembles an unconventional cast of characters, capturing their foibles and imperfections, and always rendering them with compassion as these modern-day martyrs and spiritually haunted survivors strive for some kind of redemption. Ingenious, sometimes forbidding, often absurd, and altogether original, The Saints of Rattlesnake Mountain is a stirring tribute to the lives, loves, and hopes of the faithful and the dispossessed.